Perilipin-2 promotes lipid droplet-plasma membrane interactions that facilitate apocrine lipid secretion in secretory epithelial cells of the mouse mammary gland - Monks, Jenifer; Orlicky, David J.; Libby, Andrew E.; Dzieciatkowska, Monica; Ladinsky, Mark S.; McManaman, James L. (Frontiers in Cell and Developmental Biology, 2022)
Secretory epithelial cells (sMEC) in mammary glands of lactating animals secrete lipids by a novel apocrine mechanism in which cytoplasmic lipid droplets (LD) contact and are enveloped by elements of the apical plasma membrane (APM) before being released into the lumen of the gland as membrane bound structures. The molecular properties of LD-APM contacts and the mechanisms regulating LD membrane envelopment and secretion are not fully understood. Perilipin2 (Plin2) is a constitutive LD protein that has been proposed to tether LD to the APM through formation of a complex with the transmembrane protein, butyrophilin1a1 (BTN) and the redox enzyme, xanthine oxidoreductase (XOR). Using mice lacking Plin2, we find that LD-APM contact formation does not require Plin2. However, Plin2 absence reduces the percentage of LD contacting the APM and restricts the size of the LD-APM contact zone during LD membrane envelopment. Additionally, Plin2 absence decreases levels of BTN and XOR on membranes surrounding secreted LD, reduces BTN-XOR interactions and interferes with glycocalyx remodeling at LD-APM contact sites. Plin2 absence does not appear to significantly affect lipid secretion in lactating animals, but it does reduce the initial secretion of LD at the onset of lactation. We propose that Plin2 actions modulate the physical properties and molecular interactions governing formation of LD-APM contacts and subsequent membrane envelopment of LD during apocrine lipid secretion by sMEC.